Current use and potential role of procalcitonin in the diagnostic work up and follow up of febrile neutropenia in hematological patients. Issue 6 (3rd June 2017) - Bruno, Benedetto; Busca, Alessandro; Vallero, Stefano; Raviolo, Stefania; Mordini, Nicola; Nassi, Luca; Cignetti, Alessandro; Audisio, Ernesta; Festuccia, Moreno; Corsetti, Alessandra; Depaoli, Lorella; Faraci, Maura; et al.
ABSTRACT: Introduction : Febrile neutropenia (FN) represents a life-threatening complication in hematological malignancies. Its etiology is most often due to infections even though FN of other origins, such as tumor-related fever and non-infectious inflammation, should rapidly be ruled out. Initially, C-reactive protein and, more recently, procalcitonin (PCT) have been proposed as useful biomarkers for differential diagnosis. PCT was shown to be a good biomarker of bacterial infections and their clinical outcomes. Definition of standard cut-offs and design of PCT-guided treatment protocols remain however to be defined. Areas covered : In this review, highlights on the current clinical use of PCT and its potential role as a diagnostic tool have been discussed by a panel of physicians from different areas of expertise. We provide current clinical evidence that PCT has been shown to be a reliable biomarker to differentiate fever of bacterial origin from other causes. Moreover, the Authors convened to a round-table to discuss their 'real-life experience' and offer their recommendations by a Delphi survey. Expert commentary : PCT has an important clinical role in FN. Issues such as the validation of a specific decision algorithm that includes PCT to monitor antibiotic choice and treatment duration will be addressed in prospective studies.